Graphene Oxide: A One- versus Two-Component Material - Naumov, Anton; Grote, Fabian; Overgaard, Marc; Roth, Alexandra Marina; Halbig, Christian Eberhard; Norgaard, Kasper; Guldi, Dirk Michael; Eigler, Siegfried (Journal of the American Chemical Society, 2016)
The structure of graphene oxide (GO) is a matter of discussion. While established GO models are based on functional groups attached to the carbon framework, another frequently used model claims that GO consists of two components, a slightly oxidized graphene core and highly oxidized molecular species, oxidative debris (OD), adsorbed on it. Those adsorbents are claimed to be the origin for optical properties of GO. Here, we examine this model by preparing GO with a low degree of functionalization, combining it with OD and studying the optical properties of both components and their combination in an artificial two-component system. The analyses of absorption and emission spectra as well as lifetime measurements reveal that properties of the combined system are distinctly different from those of GO. That confirms structural models of GO as a separate oxygenated hexagonal carbon framework with optical properties governed by its internal structure rather than the presence of OD. Understanding the structure of GO allows further reliable interpretation of its optical and electronic properties and enables controlled processing of GO.
CRIS-Team Scopus Importer:2023-03-07